ANALYSIS OF PROBLEM CREDIT SALES ACCOUNTING TREATMENT IN. ADIRA FINANCE BAUBAU - Mahmuda, Dewi (Institute for Research and Community Service, 2020)
This study aims to analyze the accounting treatment for non-performing loans of credit sales at PT. Adira Finance Baubau. The analysis method that being used is descriptive qualitative method. While the collecting method are field research, library research and interview. This research is conducted at PT. Adira Finance Baubau during April 2017. The results showed that the accounting treatment for non-performing problem loans of credit sales at PT. Adira Finance Baubau will be recorded as operating loss of the company. Assets in the form of cars from troubled sales will be withdrawn and repaired, then offered back to the consumers. The income of those troubled cars sales and other new cars sales are expected to recover the company's losses due to the sale of non performing loans so that the performance of PT. Adira Finance Baubau will still look stable even though the company is haunted by business risks of non-performing loans of their own car credit sales.